Trust with private and common property: Effects of stronger property right entitlements - James C. Cox; Daniel T. Hall (Games, 2010)
Is mutually beneficial cooperation in trust games more prevalent with private property or common property? Does the strength of property right entitlement affect the answer? Cox, Ostrom, Walker, et al. [1] report little difference between cooperation in private and common property trust games. We assign stronger property right entitlements by requiring subjects to meet a performance quota in a real effort task to earn their endowments. We report experiment treatments with sequential choice and strategy responses. We find that cooperation is lower in common property trust games than in private property trust games, which is an idiosyncratic prediction of revealed altruism theory [2]. Demonstrable differences and similarities between our strategy response and sequential choice data provide insight into the how these protocols can yield different results from hypothesis tests even when they are eliciting the same behavioral patterns across treatments.
Keywords: 330; trust game; private property; common property; real effort; revealed altruism theory; strategy method; sequential choice